2008
DOI: 10.1074/jbc.m804213200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of HIV-1 Integrase Variants Resistant to Strand Transfer Inhibitors

Abstract: In this study, eight different HIV-1 integrase proteins containing mutations observed in strand transfer inhibitor-resistant viruses were expressed, purified, and used for detailed enzymatic analyses. All the variants examined were impaired for strand transfer activity compared with the wild type enzyme, with relative catalytic efficiencies (k p /K m ) ranging from 0.6 to 50% of wild type. The origin of the reduced strand transfer efficiencies of the variant enzymes was predominantly because of poorer catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…InSTI mutations affected IC 50 but not m. Increases in IC 50 can be attributed to decreased affinity, resulting in the need for higher drug concentrations for inhibition. Biochemical analyses of integrase mutants indicate that the off-rate is remarkably increased relative to WT (53). This finding, coupled with our observation of a constant slope close to 1, indicates that integrase inhibitors affect WT and mutant viruses by blocking a noncooperative reaction.…”
Section: Analysis Of Resistance Mutations Using Primary Cells Vs Trasupporting
confidence: 61%
“…InSTI mutations affected IC 50 but not m. Increases in IC 50 can be attributed to decreased affinity, resulting in the need for higher drug concentrations for inhibition. Biochemical analyses of integrase mutants indicate that the off-rate is remarkably increased relative to WT (53). This finding, coupled with our observation of a constant slope close to 1, indicates that integrase inhibitors affect WT and mutant viruses by blocking a noncooperative reaction.…”
Section: Analysis Of Resistance Mutations Using Primary Cells Vs Trasupporting
confidence: 61%
“…Michaelis-Menten enzyme analysis has previously been used to determine enzyme parameters of HIV integrase (24). While 3= processing has been conclusively shown to follow nonMichaelis-Menten kinetics (25,26), there has been no similar study of HIV integrase strand transfer.…”
Section: Methodsmentioning
confidence: 99%
“…The data within the linear phase of the 3= processing reaction were used to calculate kinetic parameters by fitting the data to the Michaelis-Menten equation (24). As such, relative enzyme efficiency calculations of 3= processing activity were calculated as described above for strand transfer.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, biochemical studies have suggested that binding of INIs to HIV-1 IN proceeds by a two-step mechanism with a slow second step, and mutations that increase resistance may alter this mechanism (19,32). In addition, fast INI dissociation has been proposed to contribute to INI resistance with the N155H, T66I, and Q148R IN substitutions (14,23).…”
mentioning
confidence: 99%